Kritik Ekonomi Islam Terhadap Pemikiran Karl Marx Tentang Sistem Kepemilikan Dalam Sistem Sosial Masyarakat - Muhammad Kambali (Universitas Islam Lamongan, 2017)
The theory of Karl Marx’s Historical Materialism states that system of ownership is a necessity in the social system. Marx declares the social system development takes place in five stages. The first stage is primitive-communal society has have not recognized the system of ownership. The second stage is the stage of division of labor and the emergence of ownership. The third stage is formation of feudal society. The fourth stage is development of a capitalist community. The final stage is stage of development of the social system which is the formation of a socialist-communist society. If seen from ownership, the social-communal system is divided into three sections; the stage of primitive-communal society, the division of labor and the stages of ownership, and phase of the ownership elimination. According to Marx, the ownership of proletariat workers system suffers exploitation and alienation. Both of these things can only be solved by removing the ownership system which is replaced by the role of collective ownership. For Islamic economics, exploitation and alienation experienced by the proletariat workers are the result of inconsistencies in wealth management and distribution system in the capitalist system, not proprietary. Islamic Economics is looking at the role of individuals in managing their wealth and their distribution pattern. Keywords: Historical Materialism, Ownership, Exploitation, Alienation